The Grit Factor - Polson, Shannon (Ascent Audio, 2020)
At age nineteen, Shannon Huffman Polson became the youngest woman ever to climb Denali, the highest mountain in North America. She went on to reach the summits of Mt. Rainier and Mt. Kilimanjaro and spent more than a decade traveling the world. Yet it was during her experience serving as one of the Army's first female attack helicopter pilots, and eventually leading an Apache flight platoon on deployment to Bosnia-Herzegovina, that she learned the lessons of leadership that forever changed her life. Where did these insights come from? From her own crucibles of experience-and from other women. In writing The Grit Factor, Polson made it her mission to connect with an elite pack of tough, impressive female iconoclasts who shared with her their candid stories of combat and career. This slate of decorated leaders includes Heather Penney, one of the first female F-16 pilots, who was put on a suicide mission for 9/11; General Ann Dunwoody, the first female four-star general in the Army; Amy McGrath, the first female Marine to fly the F/A-18 in combat-and dozens of other unstoppable women who got there first, including Polson herself. With its gripping narrative and relatable takeaways, The Grit Factor is both inspiring and pragmatic, a book that will energize and enlighten current and aspiring leaders everywhere-whether male or female.